Portraits Discover techniques for approaching formal paintings - Chambers, Timothy (Califarnia Walter Foster, 2011)
lighting the subject - working from life achieving accurate proprtions - capturing a likeness
Arts (Drawing)
1 13
Keywords: Acrylic painting -- Technique; Drawing; Painting -- Technique; Portrait painting -- Technique